A Review on Algal Biopolymers - Özcimen, Didem; İnan, Benan and Morkoc, Ogün and Aybüke Efe (Journal of Chemical Engineering Research Updates, 2017)
Polymers are the most important materials we use in many areas of daily life. Without them humanity could not shape today’s world. However, major source of polymeric material is fossil fuels which decrease constantly. Therefore, alternative resources are needed to be discovered especially from biological source for sustainable polymer production. Biopolymers are polymers developed from renewable resources such as plant, animal, bacteria, fungi and algae. They can also be useful in material and many other applications. Algae are one of the most promising organisms in many aspects. Since they grow fast, contain variety of unique value added material and do not compete with food resources, and also they have high bioenergy feedstock potential. In this study, algae are considered as feedstock for biopolymer production and biopolymers derived from algae are investigated. Throughout this study algae derived biopolymers were classified as three types. First type of polymer obtained from algae are natural polymers (polysaccharides, lipids, extracellular polymeric substance). Especially polysaccharides from algae such as alginate and agar are well known for their biotechnological applications. Second type is polyhydroxyalkanoates (PHA) which accumulate in only cyanobacteria. And third type is bio-based polymers polymerized from algae derived monomer, they can have same characteristics with conventional synthetic polymer. This review study will give an idea especially about the algal biopolymers, their resources, properties, structures, application areas, production methods and their future potentials.